(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Treatment of Acute Lymphoblastic Leukemia (ALL) is mainly chemotherapy based. In the past outcome of treatment with polychemotherapy was dissatisfying. Recently success have improved as risk based polychemotherapy has been employed. Therefore in modern approach of the treatment of ALL of children assessment of risk factors has become a key issue. It has been observed in the studies abroad that response to prechemotherapy corticosteroid could be a clue to the good response to chemotherapy Objectives: The objectives of this study were to see the effects of dexamethasone on initial tumor load and to observe the relationship of the effects of prechemotherapy dexamethasone on tumor burden and the outcome of Induction of Remission. Materials and Methods: This was a prospective study carried out from January 2004 to June 2005 in the Department of Pediatric Hematology and Oncology at Bangabandhu Sheikh Mujib Medical University (BSMMU). All the cases between one to fourteen years of either genders were enrolled into the study after their confirmation as ALL. Tumor load was assessed before the beginning of prechemotherapy dexamethasone and after the day 7 of prechemotherapy dexamethasone. After reassessment of tumor load, polychemotherapy of Induction of Remission was begun. Bone marrow study was performed every seven days after starting Induction chemotherapy until the bone marrow remission was achieved. Then the effect of prechemotherapy dexamethasone on tumor load was compared with the outcome of Induction polychemotherapy. The results were analyzed maintaining standard procedure with SPSS version 10.0. Results: A total of 40 patients were enrolled into the study. Among them 21 were male and nineteen were female. Thirty were FAB L1 and ten were L2 morphologically. Reduction of tumor load was evident as estimated by peripheral blast count together with hepatic and splenic mass. Response to prechemotherapy dexamethasone was good in 21 out of 28 patients with the WBC count below 50x109/L as compared to only 4 out of 12 with the WBC count >50x109/L (P=0.013). Similarly, 21 in 24 in the group <25x109/L of Initial Blast Cell count responded good as compared to 4 in 16 with >25x109/L Initial Blast Cell count (P=0.000). Among the 25 good responders to prechemotherapy dexamethasone 24 went into remission within 7 days of induction and among the 15 poor responders only 6 went into remission within 7 days of induction (P=0.000). Conclusion: Response to pre-chemotherapy dexamethasone could be a strong guide to predict the outcome of induction chemotherapy and help in risk stratification of childhood Acute Lymphoblastic Leukemia. Bangladesh J Child Health 2016; VOL 40 (2) :79-84